2019
DOI: 10.1103/physrevd.99.072003
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of μμ pairs from open heavy flavor and Drell-Yan in p+p collisions at s=200

Abstract: PHENIX reports differential cross sections of μμ pairs from semileptonic heavy-flavor decays and the Drell-Yan production mechanism measured in p þ p collisions at ffiffi ffi s p ¼ 200 GeV at forward and backward rapidity (1.2 < jηj < 2.2). The μμ pairs from cc, bb, and Drell-Yan are separated using a template fit to unlike-and like-sign muon pair spectra in mass and p T. The azimuthal opening angle correlation between the muons from cc and bb decays and the pair-p T distributions are compared to distributions… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 80 publications
2
39
0
Order By: Relevance
“…A detailed description of the three models and a previous study for muons can be found in Refs. [49,50]. The variation of the combined acceptance and efficiency for π ± and K ± between the three models is less than 2% in p T and η.…”
Section: Hadron Simulationmentioning
confidence: 88%
“…A detailed description of the three models and a previous study for muons can be found in Refs. [49,50]. The variation of the combined acceptance and efficiency for π ± and K ± between the three models is less than 2% in p T and η.…”
Section: Hadron Simulationmentioning
confidence: 88%
“…In the TMD regime the same effect has been observed in [1] (for the same experiments that are considered in [21]), namely, about 40% deficit in the normalization that decreases with the increase of energy (see table 3 in [1]). Note, both analyses [21] and [1] have not a problem with the description of PHENIX data [47] that have a similar range of Q but measured in the collider regime. A similar problem was also observed in semi-inclusive deep-inelastic scattering (SIDIS) [48].…”
Section: Comparison To the Datamentioning
confidence: 95%
“…The mass spectra contain muon pairs from J/ψ decays, as well as significant contributions from combinations of real muons not from a J/ψ, as well as misidentified hadrons. Details about the dimuon selection to reduce the background contributions are described in [40,41].…”
Section: B J/ψ Signal Extractionmentioning
confidence: 99%